Erratum: The CMS barrel calorimeter response to particle beams from 2 to 350 GeV/c (The European Physical Journal C (2009) 60 (359-373) doi: 10.1140/epjc/s10052-009-0959-5) - (:unkn) unknown (My University, 2009)
[No abstract available]